A Reversal in Shared Prosperity in Brazil : Brazil’s Poverty and Inequality since the 2014-2016 Domestic Crisis - Ciaschi, Matias (World Bank, Washington, DC, 2020)
The Coronavirus (COVID-19) pandemic arrived in Brazil while the poorest forty percent of the population was still recovering from the 2014-2016 crisis. After boosting Latin America’s reduction in poverty and inequality for the previous decade, Brazil’s 2014-2016 crisis and recovery are a stark departure from the previous decade as Brazil’s inclusive growth turned significantly regressive. As millions of jobs were lost, Brazil’s expansive social protection system was unable to effectively serve as a countercyclical protection system. This note analyses the recently released household data from 2012 through 2019 to better understand the severity of the 2014-2016 crisis across income groups, as well as the uneven and slow recovery experienced following this crisis.